Determinants of Energy Consumption in Central Asian Countries: Panel Data Analysis - Abubakirova, Aktolkin; Omarova, Aizhan; Amaniyazova, Gulimai; Saubetova, Bibigul; Esturlieva, Aigul (International Journal of Energy Economics and Policy, 2023)
Central Asian countries (Kazakhstan, Kyrgyz Republic, Tajikistan, Turkmenistan and Uzbekistan) have been witnessing important developments in the field of economic development since gaining their independence. The increase in energy consumption, in particular, plays an important role in the development of the country's economy by triggering the development of many factors. The main purpose of this study is to empirically analyze the determinants of energy consumption in Central Asian countries. Panel data analysis covering the years 1992-2021 was used in the study. Since there are many determinants of energy consumption, the factors of economic growth, foreign direct investments and energy prices are considered appropriate in this study and it is aimed to examine the interaction of these factors with each other. The test technique used to detect the cointegration relationship in the study confirmed the cointegration relationship between the series. In other words, there is a long-term relationship between the series considered in Central Asian countries. When the estimation results are evaluated, it is seen that the results differ for each country group. It is seen that the economic growth variable, as a determinant of energy consumption, is significant in Kazakhstan, Uzbekistan and Tajikistan, the foreign direct investments series is significant in Uzbekistan and Kazakhstan, and is insignificant in Tajikistan and the Kyrgyz Republic. The results obtained for the Kyrgyz Republic were found to be insignificant for all three series.